Method for detecting content of lecithin in crude oil by using double-enzyme glassy carbon electrode

By modifying multi-walled carbon nanotubes and tin dioxide on the glass carbon electrode, and fixing choline oxidase and horseradish peroxidase, the dual enzyme GCE is prepared, and the complex, time-consuming and cost-effective detection of lecithin content in the prior art is solved, achieving a fast, accurate and economical detection effect.

CN119715750APending Publication Date: 2025-03-281 HEILONGJIANG GREEN FOOD SCIENCE RESEARCH INSTITUTE
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411842139.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The method for detecting the lecithin content in crude oil in the prior art has the disadvantages of complex operation, long detection time and high cost, and it is difficult to meet the fast, accurate and economical testing needs.

Method used

Dual enzyme GCE was prepared by immobilizing choline oxidase (ChOx) and horseradish peroxidase (HRP) on glass carbon electrodes (GCEs) with multi-walled carbon nanotubes (MWCNTs) and tin dioxide (SnO2) as modified materials to detect the content of lecithin in crude oil.

Benefits of technology

It realizes rapid and accurate detection of the lecithin content in crude oil, with the lower detection limit of 2mg/L, which has good reproducibility and stability, low cost, and can effectively replace traditional detection methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119715750A_ABST
    Figure CN119715750A_ABST
Patent Text Reader

Abstract

The invention discloses a method for detecting the content of lecithin in crude oil by using a double-enzyme glassy carbon electrode, which comprises the following steps: putting a GCE electrode into a Piranha solution, and carrying out cleaning, polishing, ultrasonic cleaning, drying and activating treatment on the GCE electrode; the preparation method comprises the following steps: adding a mixture of tin dioxide and multi-walled carbon nanotube powder into a chitosan / acetic acid solution, and carrying out ultrasonic treatment, so as to obtain an MWCNTs-SnO2-CS nano compound; the preparation method comprises the following steps: modifying GCE by using a nano-composite to obtain GCE taking MWCNTs / SnO2 / CS as a modification material; the method comprises the following steps: immobilizing choline oxidase and horse radish peroxidase on GCE taking MWCNTs / SnO2 / CS as a modification material to prepare double-enzyme GCE, inserting the double-enzyme GCE into crude oil, and measuring the content of PC in the crude oil. The double-enzyme GCE has better reproducibility and stability, and a theoretical basis is provided for rapid detection of the content of PC in crude oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for detecting the content of phosphatidylcholine (PC) in crude oil, and in particular to a method for detecting the content of phosphatidylcholine in crude oil by using a double enzyme glassy carbon electrode. Background Art

[0002] Glassy carbon electrode (GCE) is the abbreviation of glassy carbon electrode, which has the characteristics of good conductivity, high chemical stability, small thermal expansion coefficient, hard texture, good air tightness, high temperature resistance, and good hardness. Compared with other electrodes, glassy carbon electrodes have a large detection range and high stability and reproducibility. At present, most electrodes used in electrochemical sensors are glassy carbon electrodes. Glassy carbon electrodes can be used for the determination of human serum and DNA, as well as for the detection of chemical substances such as polyphenols, and have the advantages of simplicity, speed, and low cost.

[0003] In order to better realize the direct electron transfer between enzyme and electrode, the modified materials that help to improve the sensitivity of electrode are often selected in the electrode modification materials. Multi-walled carbon nanotubes (MWCNTs) have the advantages of high melting point, special electrical properties, good electrical conductivity, heat transfer performance, high thermal conductivity, etc., and can improve the conductivity of materials through composite, and have been widely used in the production of sensors. Tin dioxide (SnO2) has the advantages of good thermal stability, strong mechanical hardness and high temperature resistance, wide band gap and high chemical stability, good electrical conductivity, and can be converted into conductive oxides in the absence of oxygen. Existing studies have shown that the working electrode prepared by adding the electropolymerized film to the surface of the MWCNTs-modified electrode can complete the electron transfer between the enzyme and the electrode, and can be used for the detection of glucose content.

[0004] Phosphatidylcholine (PC) was first isolated from egg yolk and is an important component of eukaryotic membranes. Phospholipids are abundant in crude plant oils, and PC is the main component of crude oil phospholipids. In the oil refining process, hydration degumming of crude oil is a very important step. If the degumming is not sufficient and the minimum standard of phospholipid residue is not met, it will have a huge impact on the remaining refining process, not only placing a great burden on the decolorization process, but also affecting the oxidative stability and flavor of the oil, thereby affecting the shelf life of the oil and bringing a series of food safety issues. Therefore, it is particularly important to detect the content of phospholipids in crude oil. Traditional detection methods for phospholipids include ultraviolet-visible spectroscopy, Fourier transform near-infrared spectroscopy (FT-IR), high performance liquid chromatography (HPLC), thin layer chromatography (TLC), nuclear magnetic resonance spectroscopy (NMR), etc. These detection methods have the disadvantages of complex operation, long detection time, and high cost. Electrochemical detection methods have the advantages of strong stability, high sensitivity, fast detection speed, and low cost. At present, experts and scholars have conducted some useful explorations in the detection methods of electrochemical combined with biosensors, and have achieved certain applications in the rapid detection of lipids.

[0005] Biosensors are based on enzyme inhibition and are reliable tools for detecting many toxic compounds. They are widely used in clinical, food and environmental samples. Glassy carbon electrode biosensors can make up for the shortcomings of traditional methods such as chromatography and mass spectrometry, such as high cost and slow speed. They are not only commonly used in medical testing. They also have many advantages in rapid food testing, and are therefore widely used in food hygiene and safety testing.

[0006] At present, there is no report on the preparation of biosensors using MWCNTs / SnO2 composite materials modified with GCE and the use of such biosensors for the detection of PC content in crude oil. Summary of the invention

[0007] The invention aims to provide a method for detecting the lecithin content in crude oil by using a dual-enzyme glassy carbon electrode. The method selects a modification material with a higher response current value to modify GCE, improves the conductivity of the electrode, sequentially cross-links HRP and ChOx to the surface of the modified GCE by using a cross-linking agent, prepares the dual-enzyme GCE, and uses the prepared dual-enzyme GCE to detect the PC content in the crude oil, thereby providing a theoretical basis for rapidly detecting the PC content in the crude oil.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] A method for detecting the content of lecithin in crude oil using a double enzyme glassy carbon electrode comprises the following steps:

[0010] Step 1: Pretreatment and modification of GCE

[0011] Step 1. Preprocessing:

[0012] (1) placing the GCE electrode in a Piranha solution, taking it out after 10 to 20 minutes, then cleaning it with distilled water, polishing it, and finally ultrasonically cleaning it with distilled water, nitric acid, anhydrous ethanol and distilled water in sequence, taking it out, and drying it with nitrogen;

[0013] (2) Activating the cleaned GCE electrode: first, performing a cyclic voltammetry scan (-1 V to 1 V) in a sulfuric acid solution (0.5 M) until the curve is stable, and then performing a cyclic voltammetry scan (50 mV / s, 0.1 V to 0.6 V) in a potassium ferrocyanide solution until the curve is stable;

[0014] Step 1 and 2: Modification

[0015] (1) adding a mixture of 2.0-3.0 mg of tin dioxide (SnO2) and 4-6 mg of multi-walled carbon nanotube (MWCNTs) powder to 5-10 mL of a 0.1-0.5% chitosan (CS) / acetic acid transparent solution and ultrasonically treating the mixture to obtain a MWCNTs-SnO2-CS nanocomposite, which was stored at 4°C for later use;

[0016] (2) Modification of GCE

[0017] GCE was modified by MWCNTs-SnO2-CS nanocomposite to obtain GCE with MWCNTs / SnO2 / CS as modified materials;

[0018] Step 2: Preparation of dual enzyme GCE

[0019] Choline oxidase (ChOx) and horseradish peroxidase (HRP) were immobilized on GCE with MWCNTs / SnO2 / CS as the modified material to prepare dual enzyme GCE, and the addition amount of ChOx and HRP was 1-8U, preferably 2.5U, and the specific steps were as follows:

[0020] Step 21: 5-15 μL HRP solution of 1-8 U was dripped onto the surface of GCE modified with MWCNTs / SnO2 / CS, and then placed at 4°C to dry. When the surface became a thin film, 5-10 μL glutaraldehyde was dripped onto the electrode surface, and cross-linked at 37°C for 30-60 min. Then, the electrode surface was washed with PBS buffer to remove the unbound HRP.

[0021] Step 22: Take 3-5 μL chitosan / acetic acid solution and drop it on the surface of HRP electrode and let it dry;

[0022] Step 2 and 3, add 1-8U of 5-15μL ChOx, and when the surface becomes a thin film, add 5-10μL glutaraldehyde to the electrode surface, cross-link at 37°C for 30-60min, and then wash the electrode surface with PBS buffer to remove the ChOx not bound to the electrode surface;

[0023] Step 24: After drying with N2, the dual enzyme GCE is obtained and stored in a dry environment at 4°C for later use;

[0024] Step 3: Double enzyme GCE detection of PC content in crude oil

[0025] Step 3: Weigh 50 mg of soybean powder lecithin and add it to a beaker containing 100 mL of first-grade soybean oil to remove polar substances, stir well, and prepare artificial soybean crude oil;

[0026] Step 32: After adding 100 μL of 3 mg / mL PLD solution, add 1% Triton-X100 as an emulsifier and stir well for 30 min at 37°C;

[0027] Step 3: Insert the dual enzyme GCE into the artificial crude soybean oil to determine the PC content in the crude oil.

[0028] Compared with the prior art, the present invention has the following advantages:

[0029] The invention prepares a dual enzyme GCE by fixing ChOx and HRP on a GCE with MWCNTs / SnO2 / CS as an electrode modification material. The dual enzyme GCE has an obvious electrochemical response to PC. The PC content is linearly related to the reduction peak current generated within the range of 10 to 300 mg / L, and the detection limit is 2 mg / L (S / N=3). The PC content in the crude oil is detected, and the RSD is small. Compared with the detection value of HPLC, the linear correlation is good. The prepared dual enzyme GCE has better reproducibility and stability, and provides a theoretical basis for the rapid detection of the PC content in the crude oil. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Scanning electron microscopy analysis of GCE, a: Bare GCE, b: MWCNTs-SnO2-CS / GCE, c: ChOx-HRP / MWCNTs-SnO2-CS / GCE;

[0031] Figure 2 Cyclic voltammetry curves of different modified GCEs;

[0032] Figure 3 is the AC impedance spectra of different modified GCEs;

[0033] Figure 4is the relationship between the amount of ChOx added and the reduction peak current;

[0034] Figure 5 To test the relationship between the pH of the base solution and the reduction peak current;

[0035] Figure 6 The current response results of dual enzyme GCE to PC, a: GCE without enzyme modification was inserted into 1mmol·L -1 PBS buffer solution of thionine and test substrate, b: double enzyme GCE insertion containing 1mmol·L -1 PBS buffer solution of thionine and test substrate, c: double enzyme GCE insertion containing 1mmol·L -1 Thionine solution in PBS buffer solution;

[0036] Figure 7 is the square wave voltammetric curve of different PC contents;

[0037] Figure 8 is the relationship curve between reduction peak current and PC content;

[0038] Fig. 9 The linear correlation between WV and HPLC determination of PC content in crude oil;

[0039] Fig.10 The stability of the sensor for continuous measurement of soybean oil samples. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below in conjunction with the accompanying drawings, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0041] The present invention provides a method for detecting the content of lecithin in crude oil by using a dual-enzyme glassy carbon electrode, wherein all solution water used in the method is double distilled water, and the method specifically comprises the following steps:

[0042] Step 1: Pretreatment and modification of GCE

[0043] First, the GCE electrode (3mm) was placed in the Piranha solution, taken out after 15 minutes, and then cleaned with distilled water, and then polished with 0.3μm and 0.05μm aluminum oxide on chamois paper. Finally, it was ultrasonically cleaned with distilled water, nitric acid, anhydrous ethanol and distilled water for 5 minutes, taken out, and dried with nitrogen. The GCE electrode after cleaning was activated. First, a cyclic voltammetry scan (-1V~1V) was performed in a sulfuric acid solution (0.5M) until the curve was stable. Then, the electrode was cyclically scanned in a potassium ferrocyanide solution (50mV / s, 0.1V~0.6V) until the curve was stable.

[0044] 0.15g chitosan (CS) powder was weighed with an electronic balance and placed in a 250mL flask. 50mL of acetic acid solution with a mass fraction of 2.0% was added to the flask to prepare a CS / acetic acid transparent solution with a concentration of 0.3%. The solution was stirred with an electric stirrer for 30min to promote the full dissolution of CS. 2.5mg of tin dioxide (SnO2), 5mg of multi-walled carbon nanotubes (MWCNTs) powder, and a mixture of 2.5mg of tin dioxide (SnO2) and 5mg of multi-walled carbon nanotubes (MWCNTs) powder were added to 5mL of CS / acetic acid transparent solution, and ultrasonic treatment was performed for 60min to obtain SnO2-CS nanocomposites, MWCNTs-CS nanocomposites, and MWCNTs-SnO2-CS nanocomposites, which were stored at 4°C for future use. Cyclic voltammetry (CV) curves of the modified GCE were scanned in PBS buffer. The GCE modified with different materials was connected to the electrochemical workstation CHI660D and inserted into a 50mmol / L potassium ferrocyanide solution. The electrochemical impedance spectroscopy of the modified GCE was measured in the frequency range of 1 to 106Hz to screen out the best modified GCE material.

[0045] Step 2: Preparation and characterization of dual enzyme GCE

[0046] Preparation containing 100 mg·L -1The PBS buffer solution of PC is the test base solution. 2.5U horseradish peroxidase (HRP (300U / mg)) solution is dripped onto the surface of GCE modified with the best modified material, placed at 4°C and left to dry, and when the surface becomes a film, 5μL glutaraldehyde (0.5%) is added to the electrode surface, cross-linked at 37°C for 30min, and then the electrode surface is cleaned with PBS buffer to remove the unbound HRP. Then 3μL chitosan / acetic acid solution is dripped onto the surface of the HRP electrode and left to dry. 10μL choline oxidase (ChOx (13.1U / mg)) is added to GCE in an amount of 1 to 8U, and when the surface becomes a film, 5μL glutaraldehyde is added to the electrode surface, cross-linked at 37°C for 30min, and then the surface of the electrode is cleaned with PBS buffer to remove the unbound ChOx on the electrode surface, and the double enzyme GCE is obtained after N2 drying, which is stored in a dry environment at 4°C for standby use. The dual enzyme GCE was inserted into the test base solution with a pH of about 7.5 and a thionine content of 1.0 mmol·L -1 After adding 100 μL of 3 mg / mL PLD solution, the enrichment time was 30 s, and SWV was used to perform square wave voltammetry scanning in the voltage range of -0.5 V to 0.5 V and the scanning increment was 10 mV. The reduction peak current value was recorded to investigate the effect of ChOx addition and pH on the reduction peak current of the dual enzyme GCE. The dual enzyme GCE was placed in a solution containing 1 mmol·L -1 The non-enzyme modified GCE and the double enzyme GCE were inserted into the 1mmol·L -1 In the PBS buffer solution of thionine and the test base solution, the CV method was used. The voltage was in the range of -0.2 to 0.6 V, and the scanning rate was 50 mV / s. After multiple cycles of scanning, a stable CV curve was obtained to test the electrochemical response effect of the dual enzyme GCE on PC. In the test base solution, PC was treated with PLD for a period of time to obtain choline. Choline was catalyzed by ChOx to generate H2O2, which was then reduced by the fixed HRP. Then, electron transfer occurred between the oxidized HRP and the electron mediator thionine in the solution, and finally TH + The electrons obtained on the electrode surface are reduced, thus generating a reduction current, which shows that the dual enzyme GCE has an obvious electrochemical response effect on PC.

[0047] Step 3: Study on the application effect of dual enzyme GCE

[0048] 1. Establishment of PC standard curve

[0049] Use 0.1 mol / L PBS buffer to dilute and prepare PC with a content of 0 to 270 mg·L -1PC standard base solution. After adding 100μL 3mg / mL PLD solution for treatment, the dual enzyme GCE was inserted into the 5mL PC standard base solution taken each time. Under the optimal measurement conditions, SWV was used to measure the reduction peak current value in the voltage range of -0.5V to 0.5V. Each PC standard base solution with different contents was measured 5 times. The reduction peak current diagrams of different PC contents were superimposed using Origin 8.5, and the relationship between PC content and reduction peak current (Ipc) was linearly fitted.

[0050] 2. Double enzyme GCE detection of PC content in crude oil

[0051] Weigh 50 mg of soybean powder lecithin and add it to a beaker of first-grade soybean oil with 100 mL of polar substances removed, stir well to prepare soybean artificial crude oil, divide it into 5 parts, and then dilute each component with different concentrations using PBS buffer to obtain 5 parts of crude oil with different PC contents. After adding 100 μL of 3 mg / mL PLD solution for treatment, add 1% Triton-X100 as an emulsifier and stir well for 30 minutes at 37°C.

[0052] Under the optimal determination conditions, the dual enzyme GCE was inserted into 20 mL of artificial soybean crude oil, and its reduction peak current value was determined by SWV. Each sample was tested three times. Then, 5 portions of soybean crude oil with unknown PC content were taken and 30 mg·L -1 PC was determined by SWV in crude soybean oil, and the spike recovery experiment was completed. According to the method of Zhou Ling et al., the PC content in 5 crude oils was determined by high performance liquid chromatography (HPLC), and the test was conducted three times in parallel, and then compared with the test results of SWV.

[0053] 3. Study on the reproducibility and stability of dual enzyme GCE

[0054] Three prepared dual enzyme GCEs were used to detect PC content in crude oil. Under the optimal determination conditions, each electrode was immersed in crude oil and treated with 100 μL 3 mg / mL PLD solution. -1 In the PBS buffer solution of thionine, the dual enzyme GCE was scanned by SWV, and the operation was repeated six times by different personnel, and the reduction peak current value was recorded. Under the same conditions as above, 15 dual enzyme GCEs were prepared and stored in a dry and sealed environment at 4°C for 45 days. The stability of the dual enzyme GCE was tested every 72 hours during the storage process.

[0055] Step 4: Results and Analysis

[0056] 1. Scanning electron microscopy analysis

[0057] The three samples were compared and analyzed under high magnification. The scanning electron microscopy analysis results of bare GCE, MWCNTs-SnO2-CS / GCE and ChOx-HRP / MWCNTs-SnO2-CS / GCE are shown in Figure 2. Figure 1 shown.

[0058] from Figure 1 a and Figure 1 It can be observed from the comparison of b that Figure 1 b The microstructure of the sample has changed, and MWCNT and SnO2 are successfully fixed on the glassy carbon electrode. Figure 1 b and Figure 1 By comparing Figure 3 and Figure 4, it can be observed that the microstructures of the two samples have changed significantly, and HRP and Chox have been successfully immobilized on the glassy carbon electrode, indicating that the preparation of dual-enzyme glassy carbon biosensor is feasible.

[0059] 2. Modification of electrochemical properties of GCE

[0060] Modified GCEs were obtained by modifying with different modification materials. Cyclic voltammetry curves of modified GCEs were obtained by CV. Figure 2 As shown, the AC impedance spectra of different modified GCEs were obtained by AC impedance spectroscopy. Figure 3 shown.

[0061] Depend on Figure 2 It can be seen that bare GCE ( Figure 2 a) The peak current in 50mmol / L potassium ferrocyanide solution is about 40μA, and the difference between the oxidation peak potential and the reduction peak potential (⊿E) is 140mV. Figure 2 c and Figure 2 d shows that the redox peak current is slightly higher than that of the bare GCE electrode. This is because the SnO2 material can increase the conductivity and conduction of the electrons on the electrode surface. The modification of MWCNTs increases the specific surface area of ​​the electrode and improves the migration rate of electrons in the electrochemical reaction, thereby increasing the response current of the modified GCE. Figure 2 It can be seen from Figure 5 that the simultaneous modification of GCE with SnO2 and MWCNTs can obtain a stronger redox peak current and a smaller potential difference ⊿E between the oxidation peak and the reduction peak than under single conditions, which indicates that SnO2 and MWCNTs have a synergistic effect, making the electrode have a better electron transfer rate. Figure 2 b It can be seen that since ChOx and HRP are proteins, and macromolecular proteins are non-conductive, the enzyme layer hinders the transfer of electrons on the surface of the working electrode, thereby reducing the conductivity of the modified GCE. Therefore, the corresponding redox peak current obtained by the dual-enzyme GCE is smaller than that of the non-enzyme modification. However, since there are other modified materials on the dual-enzyme GCE, the redox peak current of the dual-enzyme GCE is larger than that of the bare electrode.

[0062] Depend on Figure 3 It can be seen that the electrochemical reaction of the surface of different modified GCEs was further studied by AC impedance spectroscopy. The impedance of bare GCE was about 2035Ω ( Figure 3 a), compared with SnO2-CS / GCE electrode ( Figure 3 b) The impedance value is about 427Ω, MWCNTs-CS / GCE ( Figure 3 c) The electrode impedance is about 216Ω, which is smaller than that of the bare electrode. This is mainly because SnO2 can play a conductive and electrocatalytic role, and MWCNTs have a large specific surface area, interface effect and excellent conductivity, which will facilitate the transfer of electrons and facilitate coupling with biological molecules, thereby reducing the solid-liquid interface resistance between the electrode and the electrolyte. Figure 3 d) The electrode impedance value is about 125Ω, and the impedance is further reduced, which shows lower resistance and stronger response ability. The two modified materials have a good synergistic effect, making [Fe(CN)6] 3- / 4- The redox electron pairs can easily reach the electrode surface and undergo redox reactions, showing a good electron transfer rate. The electrode impedance value modified by ChOx and HRP is around 725Ω, which increases the resistance of the modified GCE, which is consistent with the conclusion of other scholars that fixing macromolecular enzymes on the electrode will increase the electrode impedance value.

[0063] 3. Characteristics of dual enzyme GCE

[0064] At 37°C, the relationship between the amount of ChOx added to the HRP-fixed GCE and the reduction peak current is as follows: Figure 4 As shown, the relationship between the pH of the test solution and the reduction peak current is as follows Figure 5 shown.

[0065] Depend on Figure 4 It can be seen that when the amount of ChOx added to the modified GCE is 2.5U, the reduction peak current value on the electrode reaches the maximum. As the amount of ChOx added increases, the amount of enzyme immobilized on the electrode also increases, but the reduction peak current value shows a downward trend. This may be because the amount of enzyme loaded on the electrode surface has reached saturation, so the amount of ChOx added to the electrode is determined to be around 2.5U. This is similar to the optimal amount of ChOx added reported by Tig et al. at 2.5U.

[0066] Depend on Figure 5It can be seen that when the pH value of the test solution is around 7.5, the reduction peak current value increases with the increase of pH value. When the pH value reaches 7.5, the reduction peak current value reaches the maximum. When the pH value is greater than 7.5, the reduction peak current value gradually decreases. Therefore, the optimal pH value of the electrode test solution is selected as 7.5, which is consistent with the report by Serradilla et al. that the optimal pH of ChOx and HRP is in the range of 6.5 to 7.5.

[0067] The current response of the dual enzyme GCE to PC was as follows: Figure 6 shown.

[0068] Depend on Figure 6 a It can be seen that only a pair of redox characteristic peaks of thionine appeared on the GCE electrode without enzyme modification. Figure 6 aRedox peak current is greater than Figure 6 b, This is because the fixation of ChOx and HRP reduces the conductivity of the modified GCE, which further illustrates that ChOx and HRP have been successfully fixed on the electrode surface. Figure 6 b and Figure 6 c shows that when the dual enzyme GCE is inserted into the test base solution, the redox peak current increases significantly, indicating that the dual enzyme GCE has a good electrocatalytic effect on PC. Figure 6 c shows that there is a pair of stable thionine redox characteristic peaks near the voltage of 0.1 V (vs. AgCl), indicating that the dual enzyme GCE has a good cyclic voltammetric response to thionine. Figure 6 The redox peak current of b is greater than Figure 6 c, indicating that the modified material ChOx-HRP / MWCNTs-SnO2-CS plays an electrocatalytic role in the dual enzyme GCE on PC, and also indicating that the dual enzyme GCE has a good electrochemical response effect on PC. The reaction mechanism is as follows:

[0069]

[0070] 4. Application effect of dual enzyme GCE

[0071] (1) Establishment of PC standard curve

[0072] The dual enzyme GCE was placed in different PC standard base solutions. In the voltage range of -0.5V to 0.5V, the square wave voltammetry curves of different PC contents were as follows: Figure 7 The linear fitting results of different PC contents and reduction peak current values ​​are shown in Figure 8 shown.

[0073] Depend on Figure 7It can be seen that under the optimized measurement conditions, the square wave voltammograms corresponding to different PC contents were obtained according to SWV. In the PBS buffer solution (pH 7.5) without PC, the reduction peak current of thionine appeared on the electrode, and the current size was about 1 μA, and as the PC content increased, the corresponding reduction peak current value increased.

[0074] Depend on Figure 8 It can be seen that in PBS buffer solution, as the PC content increases, the reduction peak current value gradually increases. -1 The linear relationship was good within the range, and the linear regression equation was: Ipc(μA)=-0.0034x-1.042, the correlation coefficient was 0.9985, and the detection limit was 2mg·L -1 (S / N=3).

[0075] (2) Dual enzyme GCE detection of PC content in crude oil

[0076] The PC content, RSD and spike recovery results of crude oil detected by SWV and HPLC are shown in Table 1.

[0077] Table 1 Detection results and recovery of phosphatidylcholine in soybean oil

[0078]

[0079]

[0080] Note: The test results of biosensor and HPLC method are the average of 3 parallel test results.

[0081] It can be seen from Table 1 that the distribution of PC content in the prepared crude oil is reasonable and has a certain gradient. The double enzyme GCE was scanned by square wave voltammetry to determine the content of PC in the crude oil. The spiked recovery of each component was between 94.96% and 105.08%, all controlled within the range of 90% to 110%, and the relative standard deviation was less than 4.68%, indicating that the feasibility of using SWV to determine the PC content in crude oil is high.

[0082] The linear results of SWV and HPLC determination of PC content in crude oil are as follows Fig. 9 shown.

[0083] Depend on Fig. 9 It can be seen that there is a good linear correlation between the PC content in crude oil determined by SWV and HPLC, the linear equation is y = 1.04x-1.3045, and the linear correlation coefficient is r2 = 0.9929. The results show that the results of SWV and HPLC in detecting the PC content in crude oil are similar, and SWV has good accuracy and reliability in the detection of soybean oil lecithin.

[0084] (3) Detection stability of dual-enzyme GCE

[0085] The stability of the sensor in continuous measurement of samples over 15 days was evaluated (the sensor was stored in a refrigerator at 4°C when not in use). Fig.10 shown.

[0086] Depend on Fig.10 It can be seen that each point represents the average value of lecithin in soybean oil samples measured 5 times a day. It can be seen that the sensor showed good stability during the evaluation period, especially in the first 8 days, the sensor test results hardly changed, and its RSD value was only 0.83%, while after 12 days, the test results began to change significantly, and the RSD value became 12.41%. This shows that the biosensor has good stability in use over a long period of time.

Claims

1. A method for detecting the content of lecithin in crude oil using a dual enzyme glassy carbon electrode, comprising the following steps: Step 1: Pretreatment and modification of GCE Step 1. Preprocessing: (1) placing the GCE electrode in a Piranha solution, taking it out after 10 to 20 minutes, then cleaning it with distilled water, polishing it, and finally ultrasonically cleaning it with distilled water, nitric acid, anhydrous ethanol and distilled water in sequence, taking it out, and drying it with nitrogen; (2) Activating the cleaned GCE electrode: first, performing a cyclic voltammetry scan in a sulfuric acid solution until the curve is stable, and then performing a cyclic voltammetry scan in a potassium ferrocyanide solution until the curve is stable; Step 1 and 2: Modification (1) adding a mixture of 2.0-3.0 mg of tin dioxide and 4-6 mg of multi-walled carbon nanotube powder to 5-10 mL of chitosan / acetic acid solution and ultrasonically treating the mixture to obtain a MWCNTs-SnO2-CS nanocomposite, which was stored at 4° C. for later use; (2) Modification of GCE GCE was modified by MWCNTs-SnO2-CS nanocomposite to obtain GCE with MWCNTs / SnO2 / CS as modified materials; Step 2: Preparation of dual enzyme GCE Choline oxidase and horseradish peroxidase were immobilized on GCE modified with MWCNTs / SnO2 / CS to prepare dual-enzyme GCE. Step 3: Double enzyme GCE detection of PC content in crude oil The dual enzyme GCE was inserted into crude oil to determine the PC content in the crude oil.

2. The method for detecting lecithin content in crude oil using a double enzyme glassy carbon electrode according to claim 1, characterized in that The concentration of the sulfuric acid solution is 0.5M.

3. The method for detecting lecithin content in crude oil using a double enzyme glassy carbon electrode according to claim 1, characterized in that The concentration of the chitosan / acetic acid solution is 0.1-0.5%.

4. The method for detecting lecithin content in crude oil using a double enzyme glassy carbon electrode according to claim 1, characterized in that In the step 1, in the sulfuric acid solution, the conditions for the cyclic voltammetry scan are -1V to 1V, and in the potassium ferrocyanide solution, the conditions for the cyclic voltammetry scan are: 50mV / s, 0.1V to 0.6V.

5. The method for detecting lecithin content in crude oil using a double enzyme glassy carbon electrode according to claim 1, characterized in that The specific steps of step 2 are as follows: Step 21: 5-15 μL HRP solution of 1-8 U was dripped onto the surface of GCE modified with MWCNTs / SnO2 / CS, and then placed at 4°C to dry. When the surface became a thin film, 5-10 μL glutaraldehyde was dripped onto the electrode surface, and cross-linked at 37°C for 30-60 min. Then, the electrode surface was washed with PBS buffer to remove the unbound HRP. Step 22: Take 3-5 μL chitosan / acetic acid solution and drop it on the surface of HRP electrode and let it dry; Step 2 and 3, add 1-8U of 5-15μL ChOx, and when the surface becomes a thin film, add 5-10μL glutaraldehyde to the electrode surface, cross-link at 37°C for 30-60min, and then wash the electrode surface with PBS buffer to remove the ChOx not bound to the electrode surface; Step 24: After drying with N2, the dual enzyme GCE is obtained and stored in a dry environment at 4°C for later use.

6. The method for detecting the lecithin content in crude oil using a double enzyme glassy carbon electrode according to claim 1 or 5, characterized in that The added amount of ChOx and HRP is preferably 2.5U.

7. The method for detecting the lecithin content in crude oil using a double enzyme glassy carbon electrode according to claim 1 or 5, characterized in that The specific steps of step three are as follows: Step 3: Weigh 50 mg of soybean powder lecithin and add it to a beaker containing 100 mL of first-grade soybean oil to remove polar substances, stir well, and prepare artificial soybean crude oil; Step 32: After adding 100 μL of 3 mg / mL PLD solution, add 1% Triton-X100 as an emulsifier and stir well for 30 min at 37°C; Step 3: Insert the dual enzyme GCE into the artificial crude soybean oil to determine the PC content in the crude oil.

Citation Information

Patent Citations

  • Preparation method of double-enzyme glucose sensor based on graphene

    CN103033549A

  • Method for manufacturing nano platinum and multiwalled carbon nanotube modified glassy carbon electrode and method for detecting estradiol by utilizing glassy carbon electrode

    CN104198551A

  • Catalytic reduction hemoglobin electrochemical sensor

    CN105866221A

  • Method for detecting PC content in crude oil through electrochemical double-enzyme sensor

    CN110455885A

  • Preparation method of three-dimensional graphene modified electrode for detecting phospholipid in crude oil and electrode

    CN112710721A